Negative symptom dimensions in first episode psychosis: Is there a difference between schizophrenia and non‐schizophrenia spectrum disorders?. Issue 6 (25th November 2020) - Pelizza, Lorenzo; Azzali, Silvia; Paterlini, Federica; Garlassi, Sara; Scazza, Ilaria; Chiri, Luigi Rocco; Poletti, Michele; Pupo, Simona; Raballo, Andrea
Abstract: Aim: Identifying discrete dimensions that underline negative symptoms in First Episode Psychosis (FEP) could improve the understanding and the treatment of such invalidating symptomatology. The aim of this study is to examine the negative symptom structure in FEP individuals and to compare the resulting factor configurations between FEP subjects with and without Schizophrenia Spectrum Disorders (SSD vs non‐SSD). Methods: One hundred and seventy participants (88 SSD and 82 non‐SSD), aged 13–35 years, completed the Comprehensive Assessment of At‐Risk Mental States (CAARMS) and the Positive and Negative Syndrome Scale (PANSS). A principal component analysis was then performed to investigate PANSS negative symptom structure in both non‐SSD and SSD groups. Results: Whereas in the SSD sample a 3‐factor model solution (i.e., "Socio‐Emotional Disengagement", "Motor/Thought Poverty", and "Avolition/Apathy" dimensions) was identified, a 2‐factor model solution (with a mixed alogia/avolition domain in addition to a mixed socio‐emotional disengagement/expressive deficits dimension) appeared more appropriate in the non‐SSD group. Conclusions: Our results show a relevant difference in the negative symptom factor structure between SSD and non‐SSD individuals. In particular, a different specificity and significance of negative symptom models in FEP populations with diagnoses other than schizophrenia (compared to those with SSD) must be realistically considered. Notably, a "Motor/Thought Poverty" domain, which specifically includes alogia and motor retardation separately from the other PANSS negative items, appears to specifically characterize FEP young patients with the schizophrenia spectrum.